Service taxonomy and service ontologies deliver success to enterprise SOA an aid to linking the business and IT architecture through service classification. - Hill, Martyn
A lot has been written on the approach to service-oriented architecture (SOA) migration. Although they are referred to by many names, there is the strategic approach, which is of high quality and so is also costly and initially less responsive because of the analysis involved up front. Then there is the organic growth approach, in which services are developed on an as-needed basis within the context of projects, which is responsive, but leads to redundancy and the lack of vision leads to unmanageability later. Finally, there is the hybrid approach, which attempts to take the best of both of these worlds. It is so very important that the business analysis is not cast aside when developing the SOA through this hybrid approach to migration.